INTEGRATION OF INFORMATION AND COMUNICATION TECHNOLOGY INTO ISLAMIC RELIGIOUS EDUCATION TEACHER TRAINING - Miskiah Miskiah; Yoyon Suryono; Ajat Sudrajat (LPMPP Universitas Negeri Yogyakarta, 2019)
Integrating ICT in teacher training has become an absolute necessity over recent years. This research highlights the role of training as a means to improve Islamic religious education teacher competence in ICT. Specifically, the case-study research aim is to describe the level of ICT integration into the Islamic religious education training, referring to ‘education-and-training’, at a religious training center (RTC) in Palembang, Indonesia. Thirty teachers of Indonesian Islamic school (madrasah) and two facilitators at the RTC acted as informants in the research. Using the interactive model of qualitative analysis by Miles and Huberman, the research results indicated that the participants have already integrated ICT but were restricted to using presentations, especially the PowerPoint computer program. Secondly, age and technical problems became the major constraints to realize such integration. With respect to the availability of facilities, the RTC is in good category.